2019
DOI: 10.1519/jpt.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Timed Up and Go Subtasks in Frailty Syndrome

Abstract: The findings support the value of analyzing the TUG subtasks to improve understanding of mobility impairment in frailty syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 21 publications
3
32
1
5
Order By: Relevance
“…The past decade has seen tremendous advances in the development and testing of wearable sensors to evaluate important outcomes like physical performance. However, to date, wearable sensors are either very expensive [ 15 - 18 ], proprietary [ 19 , 20 ], require technicians present for testing [ 15 , 17 , 21 ], and/or involve complex programming code to process the data [ 22 ]. For example, commercially available systems that include wearable sensors, such as LEGSys or the Opal, and software to administer and score standard gait tests (eg, Timed Up and Go, or TUG test), provide a range of useful gait parameters [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has seen tremendous advances in the development and testing of wearable sensors to evaluate important outcomes like physical performance. However, to date, wearable sensors are either very expensive [ 15 - 18 ], proprietary [ 19 , 20 ], require technicians present for testing [ 15 , 17 , 21 ], and/or involve complex programming code to process the data [ 22 ]. For example, commercially available systems that include wearable sensors, such as LEGSys or the Opal, and software to administer and score standard gait tests (eg, Timed Up and Go, or TUG test), provide a range of useful gait parameters [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we identified older adults who took a longer time to complete the TUG test to be at higher risk of frailty, implying that less than optimal functional mobility and dynamic balance results in susceptibility to being frail. This finding is supported by a study conducted among Brazilian older adults, whereby time taken to complete the TUG was significantly longer among frail older adults [43]. Although the parameter of ‘slowness’ measured using the gait speed test is one of the five Fried’s frailty criteria, the TUG test has been identified as a reliable measure of frailty in its own right [44].…”
Section: Discussionmentioning
confidence: 68%
“…We found that despite the high sensitivity and accuracy of motion capture cameras [44], this technology is not ideal for TUG, given the cameras’ restricted field view, preventing simultaneous capture of all body sensors throughout all TUG phases. In a previous study using the Qualisys™ MCC, subjects repeated the TUG test six times, prioritizing different TUG phases during distinctive test repeats, and while wearing approximately 50 body markers [45]. Despite the robust procedure, the physical field of views of the cameras made it impossible to analyze biomarkers such as the complete gait cycle [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study using the Qualisys™ MCC, subjects repeated the TUG test six times, prioritizing different TUG phases during distinctive test repeats, and while wearing approximately 50 body markers [45]. Despite the robust procedure, the physical field of views of the cameras made it impossible to analyze biomarkers such as the complete gait cycle [45]. MCC further require a large physical space to house the system, cumbersome procedures (e.g.…”
Section: Discussionmentioning
confidence: 99%